Association of CT Scan Finding of Bronchial Carcinoma with Fiber Optic Bronchoscopy (Chest & Heart Journal, 2021)
Background: Bronchoscopy is highly sensitive investigation for patients with suspected lung malignancy. Beside histology, a cytological diagnosis is also possible with the help of bronchoscopy.Objective: The main objective of the present study was to evaluate the effectiveness of fiber optic bronchoscopy and CT in the diagnosis of bronchial carcinoma.Methods: This cross sectional study was conducted in the Department of Pathology and Department of Respiratory Medicine, National Institute of Diseases of the Chest & Hospital, Mohakhali, Dhaka, between January 2019 and December 2019. Patients in whom an endoscopically visible lung mass and who had a definite cytological or histological diagnosis of lung cancer were included in the study. The diagnosis of pulmonary malignancy could have been established by bronchoscopy. Out of total 50 patients with suspected bronchial carcinoma were included in the study. A detailed clinical history, physical examinations was done before hand and necessary investigations were also done. Selected patients with chest xray and CT scan and clinical findings consisting with lung cancer were subjected for flexible fiberoptic video bronchoscopy after obtaining well informed written consent. All flexible bronchoscopies were carried out or supervised by the same bronchoscopist using the Olympus BF-1T150 fiberoptic bronchoscope. Collected data were compiled and appropriate analyses were done by using computer based software, Statistical Package for Social Sciences (SPSS) version 23.0.Results: In this study 50 patients with bronchial carcinoma, majority 25 (50.0%) patients belonged to age 41 to 60 years, male: female ratio was 3.5:1. All 50(100.0%) patients were presented with cough followed by 43(86.0%) with fever, 39(78.0%) with haemopytysis, 38(76.0%) with weight loss and 36(72.0%) patients presented with chest pain. Regarding pathologic findings, 18(36.0%) patients was found were squamous cell carcinoma followed by 11(22.0%) were small cell carcinoma, 10(20.0%) were adenocarcinoma and 5(10.0%) were large cell carcinoma. In radiographic findings, 18(36.0%) patients was found in lobar collapse followed by 13(26.0%) were pulmonary masses, 11(22.0%) were pulmonary consolidation, 6(12.0%) were unilateral hilar disease and 2(4.0%) in mediastinal/subcarinal disease. The validity of CT findings evaluation for malignancy was correlated by calculating sensitivity 82.2%, specificity 60.0%, accuracy 80.0%, positive predictive value 94.9% and negative predictive value 27.3%.Conclusion: Our results show that lung cancer diagnosis is essentially achieved by CT and bronchoscopic techniques. The association of bronchoscopy and CT is useful in the accurate diagnosis of lung cancer, since the occurrence of false-positive results of CT is minimized, improving the specificity of the method. On the other hand, the utilization of CT to detect the presence of peripheral lesions, which increase the incidence of false-negative results of bronchoscopy, allows a better descission for the OT predictive diagnosis of lung cancer which occasionally gives false positive result is minimized & improved by combination with FOB, increasing the diagnostic accuracy.Chest Heart J. 2020; 44(1) : 20-27